2016
DOI: 10.5430/ijhe.v5n4p96
|View full text |Cite
|
Sign up to set email alerts
|

Improving Academic Writing in Nursing Education

Abstract: Background: At a specialist nursing education in intensive care, located at a University college in Sweden, there was a desire among the faculty to develop their ability to support specialist nursing students in their academic development, as well as in their academic writing, to improve the overall quality of the master theses. A quality improvement design, the Plan, DO, Study, Act (PDSA) cycle was applied. Two graduating classes of specialist nursing students and two faculty members were involved in the qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
2
1
0
Order By: Relevance
“…Accordingly, the understanding of scientific, theoretical and ethical perspectives can be both depicted and applied. This is in line with Mattsson [45] who explained the importance of the three approaches to learning and their relationship to the given clinical education context.…”
Section: Resultssupporting
confidence: 86%
“…Accordingly, the understanding of scientific, theoretical and ethical perspectives can be both depicted and applied. This is in line with Mattsson [45] who explained the importance of the three approaches to learning and their relationship to the given clinical education context.…”
Section: Resultssupporting
confidence: 86%
“…Our study also found that the students reflected on what ‘evidence’ is through the process of conducting clinical projects, which confirms findings from other studies ( André et al, 2016 ; Roca et al, 2018 ) that highlight the importance of providing students with an opportunity to independently work on complex assignments that go beyond searching for relevant literature and attending lectures ( Lundgren & Halvarsson, 2009 ; Mattila et al, 2005 ; Mattsson, 2016 ).…”
Section: Discussionsupporting
confidence: 89%
“…Students have also stated that by working on their bachelor thesis they expected to gain valuable knowledge needed for their professional practice in the health care services ( Henttonen et al, 2021 ). Working on a bachelor thesis is a complex process and includes learning activities that consist of more than just reading the literature and attending lectures and seminars ( Lundgren & Halvarsson, 2009 ; Mattila et al, 2005 ; Mattsson, 2016 ). It provides the students with an opportunity to independently work on a complex assignment, formulate a topic, select relevant literature, and process the data ( André et al, 2016 ; Roca et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%